Performance analysis of a high-efficiency multi-bed active magnetic regenerator device. (25th November 2021) - Masche, M.; Liang, J.; Dall'Olio, S.; Engelbrecht, K.; Bahl, C.R.H.
Highlights: A magnetocaloric device with a parallel flow system was tested by DTU. The device produced a maximum cooling power of 815 W over a 5.6 K-span at 1.2 Hz. A maximum second-law efficiency of 20.5% was achieved. The device offers great freedom to adjust the cold and hot blow fractions. Abstract: We present the performance of an active magnetic regenerator prototype with a multi-bed concept and parallel flow circuit. The prototype applies a two-pole permanent magnet (maximum magnetic flux density of 1.44 T) that rotates over 13 tapered regenerator beds mounted on a laminated iron yoke ring. Each bed is filled with about 262 g of spherical particles, distributed in layers of ten alloys of La(Fe, Mn, Si)13 Hy (CALORIVAC HS) with different Curie temperatures. Other important features are the solenoid valves, the monitoring of the temperatures exiting each bed at the cold side, and a torque meter used to measure the magnetic power required to drive the cycle. The opening behavior of the solenoid valves (i.e., the blow fraction) could be adjusted to correct flow imbalances in each bed. The device provided a maximum cooling power of about 815 W at a cycle frequency of 1.2 Hz, a utilization of 0.36, and a hot reservoir temperature of 295 K while maintaining a 5.6 K-temperature span with a coefficient of performance of 6.0. In this case, the second-law efficiency was 11.6%. The maximum second-law efficiency of 20.5%, which represents one of the largest for a magnetocaloric device, was obtained at a cycle frequency of 0.5 Hz, a utilization of 0.34, and a hot reservoir temperature of 295 K at a temperature span of 10.3 K. Under these conditions, the device absorbed a cooling load of 288 W with a coefficient of performance of 5.7. It was also shown that an unbalanced flow due to different hydraulic resistance through the beds can cause cold side outlet temperature variations, which reduce the system performance, demonstrating the importance of a well-functioning, balanced flow system.